One-Carbon Metabolism Regulates Embryonic Stem Cell Fate Through Epigenetic DNA and Histone Modifications: Implications for Transgenerational Metabolic Disorders in Adults - Van Winkle, Lon J.; Ryznar, Rebecca (Frontiers in Cell and Developmental Biology, 2019)
Abstract Human (h) and mouse (m) embryonic stem (ES) cells need specific amino acids to proliferate. mES cells require threonine (Thr) metabolism for epigenetic histone modifications. Thr is converted to glycine and acetyl CoA, and the glycine is metabolized specifically to regulate trimethylation of lysine (Lys) residue 4 in histone H3 (H3K4me3). DNA methylation and methylation of other H3 Lys residues remain unimpaired by Thr deprivation in mES cell culture medium. Similarly, hES cells require methionine (Met) to maintain the Met-SAM (S-adenosylmethionine) cycle of 1-carbon metabolism also for H3K4me3 formation. H3K4me3 is needed specifically to regulate and maintain both mES and hES cell proliferation and their pluripotent states. Better understanding of this regulation is essential since treatment of human diseases and disorders will increasingly involve hES cells. Furthermore, since ES cells are derived from their progenitor cells in preimplantation blastocysts, they serve as models of 1-carbon metabolism in these precursors of all mammalian tissues and organs. One-carbon metabolism challenges, such as a maternal low protein diet (LPD) during preimplantation blastocyst development, contribute to development of metabolic syndrome and related abnormalities in adults. These 1-carbon metabolism challenges result in altered epigenetic DNA and histone modifications in ES progenitor cells and the tissues and organs to which they develop. Moreover, the modified histones could have extracellular as well as intracellular effects, since histones are secreted in uterine fluid and influence early embryo development. Hence, the mechanisms and transgenerational implications of these altered epigenetic DNA and histone modifications warrant concerted further study.